Comparative analysis of bacterial and microalgal natural astaxanthin: Part I — Focus on composition, molecular interactions, antioxidant activities, physicochemical and biological functions - Mussagy, Cassamo U.; Caicedo-Paz, Angie V.; Farias, Fabiane O.; Tropea, Alessia; La Tella, Roberta; Guzmán-Flores, Juan M.; Mondello, Luigi; Herculano, Rondinelli D. [UNESP]; Filho, Paulo E.L.L. [UNESP]; Piazza, Rodolfo D. [UNESP]; Marques, Rodrigo F.C. [UNESP]; Giuffrida, Daniele; et al. (Elsevier, 2025)
Astaxanthin (AXT) has increasingly become an integral part of our daily lives, recognized for its extensive health benefits, particularly its potent antioxidant properties that help protect cells from oxidative stress and damage. This comparative research work focuses on the composition, molecular interactions, antioxidant activities, physicochemical properties, and biological processes of AXT from the microalga Haematococcus pluvialis and the bacterium Paracoccus carotinifaciens. The Part I of this study aims to address the following key questions: What are the differences in composition between Haematococcus and Paracoccus? What do the molecular interactions in intracellular recovery reveal? What are the antioxidant activities? How does the AXT type exhibit its physicochemical behavior? How do they perform in specific biological functions? Key findings reveal that H. pluvialis contains a more diverse array of AXT esters, enhancing solubilization during intracellular recovery compared to the free AXT form in P. carotinifaciens. Antioxidant assays demonstrate that H. pluvialis exhibits superior radical scavenging activity. Furthermore, stability assessments indicate that esterified AXT from H. pluvialis outperforms the free forms from P. carotinifaciens. Molecular target predictions suggest potential health benefits from both sources, with H. pluvialis likely impacting a broader range of biological pathways. This research underscores the commercial viability of H. pluvialis for human consumption and highlights the need for further exploration of P. carotinifaciens as a sustainable source of AXT for animal nutrition.
Keywords: Application; Astaxanthin; Biological process; Functional food; Haematococcus pluvialis; Paracoccus carotinifaciens